Cardiological Database Management System as a Mediator to Clinical Decision Support - Pappas, C.; Mavromatis, A.; Maglaveras, N.; Tsikotis, A.; Pangalos, G.; Ambrosiadou, V. (Methods of Information in Medicine, 1996)
An object-oriented medical database management system is presented for a typical cardiologic center, facilitating epidemiological trials. Object-oriented analysis and design were used for the system design, offering advantages for the integrity and extendibility of medical information systems. The system was developed using object-oriented design and programming methodology, the C++ language and the Borland Paradox Relational Data Base Management System on an MS-Windows NT environment. Particular attention was paid to system compatibility, portability, the ease of use, and the suitable design of the patient record so as to support the decisions of medical personnel in cardiovascular centers. The system was designed to accept complex, heterogeneous, distributed data in various formats and from different kinds of examinations such as Holter, Doppler and electrocardiography.
Keywords: Cardiological Database Management System; Object-oriented Programming